Development of parametric space for the vortex generator location for improving thermal compactness of an existing inline fin and tube heat exchanger. (5th April 2016) - Arora, Amit; Subbarao, P.M.V.; Agarwal, R.S.
Highlights: Parametric space for the effective locations of upwash delta winglets. Winglet location for maximum augmentation in a fin-and-tube heat exchanger. Thermo-hydraulically optimal locations of the winglets exist in clusters. Winglets augment heat transfer due to the bulk mixing of near wall and core fluid. Abstract: Heat transfer augmentation due to the intentional generation of longitudinal vortices in a fin-and-tube heat exchanger strongly depends on the location of the generators. This combined experimental and numerical study in the Reynolds number range from 1415 to 7075 is a step forward in the direction of product development. It is aimed at first determining the parametric space for the locations of delta winglet type vortex generators (DVG) which are effective for heat transfer augmentation. Thereafter the locations suitable for maximum augmentation are found. This comprehensive investigation considers the delta winglets attacking the oncoming flow over a wide range of angles ranging from 15° to 60°. It is recognized that the winglet location suitable for maximum augmentation can be defined in two ways, one that delivers maximum enhancement while ignoring the increase in flow loss and the other that incurs justifiable increase in the flow loss. A study of the flow structure reveals that the wake of each tube of an inline fin and tube heat exchanger occupies almost the entire intervening space between the two consecutive tubes. This makes the wetted fin area thermally under-productive due to poor heat transfer coefficients. Augmenting heat transfer in the tube wake is very important for the compact design of such heat exchangers. It is observed that well positioned winglets are effective in reducing the ovality of the isotherms. Such a change is a manifestation of more effective and homogeneous heat transfer from the fin.